Osthole Ameliorates Renal Fibrosis in Mice by Suppressing Fibroblast Activation and Epithelial-Mesenchymal Transition - Zhang, Suping; Huang, Qian; Cai, Xiaoxia; Jiang, Shan; Xu, Nan; Zhou, Qin; Cao, Xiaoyun; Hultström, Michael; Tian, Jiong; Lai, En Yin (Frontiers in Physiology, 2018)
Renal fibrosis is a common pathway of virtually all progressive kidney diseases. Osthole (OST, 7-Methoxy-8-(3-methylbut-2-enyl)-2-chromenone), a derivative of coumarin mainly found in plants of the Apiaceae family, has shown inhibitory effects on inﬂammation, oxidative stress, fibrosis and tumor progression. The present study investigated whether OST mediates its effect via suppressing fibroblast activation and epithelial-mesenchymal transition (EMT) in unilateral ureteral obstruction (UUO)-induced renal fibrosis in mice. Herein, we found that OST inhibited fibroblast activation in a dose-dependent manner by inhibiting the transforming growth factor-β1 (TGFβ1)-Smad pathway. OST also blocked fibroblast proliferation by reducing DNA synthesis and downregulating the expressions of proliferation- and cell cycle-related proteins including proliferating cell nuclear antigen (PCNA), CyclinD1 and p21 Waf1/Cip1. Meanwhile, in the murine model of renal interstitial fibrosis induced by UUO, myofibroblast activation with increased expression of α-smooth muscle actin (α-SMA) and proliferation were attenuated by OST treatment. Additionally, we provided in vivo evidence suggesting that OST repressed EMT with preserved E-cadherin and reduced Vimentin expression in obstructed kidney. UUO injury-induced upregulation of EMT-related transcription factors, Snail family transcriptional repressor-1(Snail 1) and Twist family basic helix-loop-helix (BHLH) transcription factor (Twist) as well as elevated G2/M arrest of tubular epithelial cell, were rescued by OST treatment. Further, OST treatment reversed aberrant expression of TGFβ1-Smad signaling pathway, increased level of proinflammatory cytokines and NF-kappaB (NF-κB) activation in kidneys with obstructive nephropathy. Taken together, these findings suggest that OST hinder renal fibrosis in UUO mouse mainly through inhibition of fibroblast activation and EMT.